Education as a Process of Humanization: A Philosophical and Scientific Examination of the Development of the Whole Human Being - Atika Zikri; Amril Amir; Nurizzati Nurizzati (CV. Syntax Corporation Indonesia, 2026)
The reduction of education to a technocratic process that is only oriented towards cognitive achievement has ignored basic human values. This research aims to analyze the essence of education as a humanization process by integrating philosophical and scientific perspectives, as well as identifying the main dimensions in the development of the whole human being. The method used was a systematic literature review of 28 articles from Scopus, Web of Science, and the Garuda Portal for the 2014–2024 period with the keywords